FILSAFAT PANCASILA SEBAGAI PEDOMAN HIDUP BANGSA INDONESIA - Vivin Frindiyani; Akih Mohamad Naehu; Rosidah Rosidah (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT Research on Pancasila philosophy as a way of life for the Indonesian nation has been conducted by Semadi (2019), Junaedi (2018), Soedarso (2006). This research aims to analyze the philosophy of Pancasila as the way of life for the Indonesian nation. This research can be classified as philosophical research, using qualitative methods as a research step and literature review as a reference source. The problem that occurs is the philosophical relationship between the state and the foundation of the Pancasila precepts as the way of life for the Indonesian nation, so we feel the need to examine it. This research has been carried out in many universities in Indonesia, but it has never been done at SMKN 7 Kota Serang. In such a case, the philosophy of Pancasila as the guideline for the Indonesian nation which is applied must be in line with the unity of the Pancasila precepts. Pancasila philosophy is considered, trusted and believed to be something (reality, norms, values) that is the most correct, fairest, wisest, best, fairest and most appropriate for the Indonesian nation. Furthermore, Pancasila as the basis of state philosophy is essentially a state spiritual principle. Where Pancasila in the administration of the State is domiciled as the source of all sources of law in Indonesia.